Crowdfunding and sustainable urban development in emerging economies - Benna, Umar G., 1942-; Benna, Abubakar U., 1980- (IGI Global, 2018)
"This book explores the theoretical foundation and development values influencing the choices by the key development actors in developing countries of the types of activities and the tools for undertaking them and highlights how public institutions use digital technologies to transform their activities in their cities and the results achieved"- Resumé vydavatel
Keywords: crowdfunding -- rozvojové země; urbanismus -- rozvojové země; udržitelný rozvoj -- rozvojové země; crowdfunding -- developing countries; city planning -- developing countries; sustainable development -- developing countries; elektronické knihy; sborníky; electronic books; papers of several authors